An integrated evaluation of land surface energy fluxes over China in seven reanalysis/modeling products. Issue 16 (24th August 2017) - Li, Hongyu; Fu, Congbin; Guo, Weidong
Abstract: An integrated evaluation of monthly mean land surface energy fluxes over China in seven reanalysis and land model products during the period 1979–2015 is conducted. Observations from seven field sites are used to evaluate these flux products, including four reanalysis data sets and three produced by off‐line land surface models. In general, the expected seasonal variations and spatial patterns in major climatic regimes are well reproduced by all reanalysis and modeling products. However, large differences among the four reanalysis products are found, while the three off‐line land surface modeling products correlate well with each other. Looking at the Bowen ratio, it is found that the off‐line land surface models convert a larger fraction of surface available energy into sensible heat flux compared to the reanalysis products in all climatic regimes. There are three centers of high interannual variability in sensible heat located in West China, Northeast China, and the eastern Inner Mongolia, respectively. In addition, the sensible heat flux agrees better with observations at grassland sites than at forest sites, while the latent heat flux and net radiation are significantly overestimated at forest sites in all the flux products. Besides, mean square errors of the fluxes are decomposed into biases, correlations, and differences in standard deviation. Finally, based on a ranking system adopted to quantitatively evaluate the performance of each data set, it is found that the surface energy fluxes in ERA‐Interim and JRA‐25 agree well with observations and the ensemble mean of all these products remains reasonably realistic as well. Key Points: The first integrated evaluation of currently available surface energy fluxes products over China Off‐line land surface models tend to convert a larger fraction of surface available energy into sensible heat flux compared to the reanalysis products The mean square errors of the flux products mostly originate from the bias term